Sleep quality of vulnerable elderly people: associated factors - Ariene Angelini dos Santos-Orlandi; Ana Carolina Ottaviani; Elén dos Santos Alves; Tábatta Renata Pereira de Brito; Keika Inouye (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To identify factors associated with poor sleep quality in elderly dependent individuals in social vulnerability. Method: Cross-sectional study with 59 elderly dependent individuals assisted by Family Health Units in São Carlos/SP. The following tools were used: Katz Index, Lawton and Brody Scale, Pittsburgh Sleep Quality Index, Addenbrooke’s Cognitive Examination Revised, Fried’s Frailty Phenotype, Geriatric Depression Scale (15 items), Perceived Stress Scale, Family APGAR, Social Support Scale from the Medical Outcomes Study, and World Health Organization Quality of Life, abbreviated and “old” versions. Results: The majority of participants were women (52.5%), aged 60-74 years (71.1%), and had poor sleep quality (76.2%). Stress (OR=1.12; 95%CI=1.02-1.22) and polypharmacy (OR=7.39; 95%CI=1.22-44.73) increased the chances of poor sleep quality, while physical activity decreased these chances (OR=0.15; 95%CI=0.02-0.79). Conclusion: Stress and polypharmacy are associated with poor sleep quality in elderly dependent individuals.